The Effect of Tax Incentives, Taxpayer Awareness, Tax Sanctions and Implementation of E-filling on MSME Taxpayer Compliance - Putu Indrika Sari; N L P Norma Dewi Abdi Pradnyani; P Adi Suprapto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2022)
This study aims to determine the effect of tax incentives, taxpayer awareness, tax sanctions, and the application of e-filling on MSME taxpayer compliance at the Gianyar Pratama Tax Service Office. This study is a quantitative study using primary data obtained from the answers to questionnaires distributed to respondents and measured using a likert scale. Determination of the sample in this study using incidental sampling technique and obtained a total sample of 100 MSME taxpayers registered at the KPP Pratama Gianyar. Testing the variables in this study using the Partial Least Square (PLS) method using the SmartPLS 3.0 application. The results of the study indicate that tax incentives, taxpayer awareness, tax sanctions, and the implementation of e-filling have a positive and significant impact on MSME taxpayer compliance. Further research is expected to be able to add or use other variables besides the variables used in this study so that further research is better.